The roles of nuclear focal adhesion kinase (FAK) on Cancer: a focused review - Zhou, Jin (J Exp Clin Cancer Res, 2019)
FAK is a tyrosine kinase overexpressed in cancer cells and plays an important role in the progression of tumors to a malignant phenotype. Except for its typical role as a cytoplasmic kinase downstream of integrin and growth factor receptor signaling, related studies have shown new aspects of the roles of FAK in the nucleus. FAK can promote p53 degradation through ubiquitination, leading to cancer cell growth and proliferation. FAK can also regulate GATA4 and IL-33 expression, resulting in reduced inflammatory responses and immune escape. These findings establish a new model of FAK from the cytoplasm to the nucleus. Activated FAK binds to transcription factors and regulates gene expression. Inactive FAK synergizes with different E3 ligases to promote the turnover of transcription factors by enhancing ubiquitination. In the tumor microenvironment, nuclear FAK can regulate the formation of new blood vessels, affecting the tumor blood supply. This article reviews the roles of nuclear FAK in regulating gene expression. In addition, the use of FAK inhibitors to target nuclear FAK functions will also be emphasized.